Conservative management in puerperal hemorrhage due to placenta accreta - Martínez Ramón, Gloria Paz (2024)
The placenta accreta spectrum is on the rise due to multiple causes, especially theincrease in cesarean sections. Diagnosis is challenging, as most are associated withhemorrhage after delivery. Prenatal morphologic ultrasonography should evaluatefor signs of suspected placental accreta. We present the case of a patient diagnosedwith placenta accreta after abundant puerperal hemorrhage 48 hours after delivery,which required two uterine curettages and the administration of intramuscularmethotrexate. As for treatment, although previously radical management waschosen, the current trend is conservative management in order to preserve thepatient's fertility.